Systematic palaeontology of marine carboniferous fossils from Bukit Buchu, Terengganu, Peninsular Malaysia / Tang Hung Yung - Tang , Hung Yung (2022)
Bukit Buchu has been known for its well-preserved Carboniferous marine fossils. In this study, six detailed geological mapping localities cover the western and eastern hillsides of Bukit Buchu. Three fossiliferous horizons were identified at the eastern hillside, but the western hillside yielded no fossil. The Bukit Buchu sedimentary sequence is informally called Bukit Buchu Beds and is estimated at more than 1100 m thick. Seventeen species of marine invertebrates were identified and described. These faunas include one new genus and species of Cyclida, Malayacyclus terengganuensis Tang et al., 2021, a species of coral, Cladochonus sp., a new species of trilobite Linguaphillipsia buchuensis n. sp. and fourteen species of brachiopods, Argentiproductus aff. margaritacea (Phillips, 1836), Antiquatonia sp., Brachythyrina (Brachythyrina) sp., Eomarginifera sp., Hustedia sp., Leptagonia analoga (Phillips, 1836), Linoproductus sp., Oehlertella sp., Pleurogpugnoides sp., Podtsheremia cf. thomasi Roberts, 1971, Pugilis sp., Punctospirifer cf. pahangensis Muir-Wood, 1948, Rugosochonetes sp., and Vitiliproductus aff. gröberi (Krenkel, 1913). The fauna is determined as Visean age (Early Carboniferous). Bukit Buchu Beds is best correlated to the Charu Formation instead of Panching Limestone based on the interpreted geological age, faunal affinities, and the lithostratigraphic data. During the Early Carboniferous, the East Malaya Block was located close to the Indochina and South China blocks near the palaeoequator. The new finding suggests that the Visean marine environment of East Malaya and Indochina blocks is the migratory route for brachiopods and trilobites from the Eastern Tethys to Australia in the southern region.